The handbook of competency mapping : understanding, designing and implementing competency models in organizations - Sanghi, Seema, 1961- (Los Angeles : SAGE, 2016)
A must-have resource for HR managers and professionals understand, develop, manage and map competencies within their organizations.
Introduction to Competency -- Mapping Competency Models - -- Competency-based Applications -- Issues Related to Developing Competency Models -- Formation of a Competency Framework -- Writing Competencies -- Assessment Centres - - Competency-based Interviewing -- Resistance and Recommendations -- Generic Competencies -- Competency Model for HR -- Generic Competency Model for Leadership Role in Any Organization -- Leadership Competency Model for Automobile Industry -- Competency Framework for Academic Institutions -- Experiential Sharing.
Includes bibliographical references (pages 333-336) and index.
Keywords: Core competencies; Employees -- Training of; Management; Organizational effectiveness; Strategic planning